The Post-thrombotic Syndrome in Young Women: Retrospective Evaluation of Prognostic Factors - Biguzzi, Eugenia; Mozzi, Enrico; Alatri, Adriano; Taioli, Emanuela; Moia, Marco; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1998)
Post-thrombotic syndrome (PTS) in young women may cause impairment in the quality of life of otherwise healthy people. We aimed to evaluate the prevalence of PTS and its risk factors in young women.We evaluated 51 women with at least one previous episode of symptomatic, objectively documented deep vein thrombosis (DVT) before the age of 40. Each patient asked for symptoms had a physical examination, a color-coded Doppler ultrasonography of the superficial and deep venous system and an extensive laboratory evaluation for the congenital and acquired coagulation abnormalities predisposing to thrombosis. The median follow-up was 47 months.PTS was absent in 37%, mild in 55%, moderate in 4% and severe in 4% of patients. No correlation was found between PTS and the presence of coagulation abnormalities, triggering factors, recurrences, use of elastic stockings for one year after DVT, degree of recanalization, presence of superficial reflux. Patients with a body mass index (BMI) >22 had an adjusted ratio of 4.7 (98 CI: 1.0-23.3) of developing the PTS. Though severe and moderate PTS are rare, mild PTS is present in the majority of young women after DVT. A BMI >22 is associated to the risk of developing PTS. Attempt to control weight in women after DVT should be considered and studied to prevent PTS.